2015
DOI: 10.1371/journal.pone.0129285
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sperm Motility and Capacitation Induce Chromosomal Aberration of the Bovine Embryo following Intracytoplasmic Sperm Injection

Abstract: Intracytoplasmic sperm injection (ICSI) has become the method of choice to treat human male infertility. One of the outstanding problems associated with this technique is our current lack of knowledge concerning the effect of sperm capacitation and motility upon the subsequent development of oocytes following ICSI. In the present study, we first examined the capacitation state of sperm exhibiting normal motility, along with sperm that had been activated, and examined the effect of reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
0
17
0
6
Order By: Relevance
“…Kato and Nagao suggested that capacitated sperm exhibiting hyperactivated motility induce chromosomal aberration in bovine ICSI‐embryos owing to a high mitochondrial activity and increased production of reactive oxygen species (Kato & Nagao, ). This was likely not influencing our present study because the spermatozoa were not selected based on motility.…”
Section: Discussionmentioning
confidence: 99%
“…Kato and Nagao suggested that capacitated sperm exhibiting hyperactivated motility induce chromosomal aberration in bovine ICSI‐embryos owing to a high mitochondrial activity and increased production of reactive oxygen species (Kato & Nagao, ). This was likely not influencing our present study because the spermatozoa were not selected based on motility.…”
Section: Discussionmentioning
confidence: 99%
“…After an injection it is possible to activate oocytes, in order to provide extrusion of the second polar body, by influence of 7 % etanol for 3-5 minutes [17,25]. However, outer activation of an oocyte can cause virginal reproduction [18].…”
Section: биология и биотехнологииmentioning
confidence: 99%
“…Oocytes demonstrating extrusion of the second PB after 3-4 hours after activation are considered to be insemintated [17,25].…”
Section: биология и биотехнологииmentioning
confidence: 99%
“…The evaluation of chromatin damage is an important aspect of sperm analysis because some sperm with chromatin abnormalities can fertilize the oocyte, but the embryo development is impaired, which leads to a high rate of embryonic death (ELLINGTON et al, 1998;KHALIFA et al, 2008;KATO;NAGAO, 2015).…”
Section: Chromatin Integritymentioning
confidence: 99%